Research Notes. The Past is the Past—Or is it? The Use of Retrospective Accounts as Indicators of Past Strategy - Golden, Brian (Academy of Management Journal, 1992)
This study challenges the common assumption that retrospective accounts of business strategy are reliable and valid. Chief executives reported their firms? current strategies, and two years later, they reported their firms? strategies of two years earlier. Of these retrospective accounts, 58 percent did not agree with the previous and validated reports of past strategy. Retrospective errors appear to occur systematically and may be attributable to faulty memory or to attempts to cast past behaviors in a positive light.